2014
DOI: 10.1111/rec.12126
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Wedge‐tailed Shearwaters and Changes in Soil Nutrients following Removal of Alien Mammalian Predators and Nitrogen‐fixing Plants at Kaena Point, Hawaii

Abstract: A predator‐proof fence was built at Kaena Point Natural Area Reserve, Hawaii in 2010 as part of an ecosystem restoration project. All non‐native mammalian predators were removed and are now excluded. Non‐native plants are being removed and native species are being outplanted. We monitored abundance and reproduction of Puffinus pacificus (wedge‐tailed shearwaters), collected soil samples before and after fence construction, and examined the relationship between changes in shearwater numbers and soil nutrients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This includes peninsula‐fenced ecosanctuaries: pest‐exclusion fencing at the peninsula neck aims to maintain low or close‐to‐zero pest abundance, despite potential reinvasion around the coastal fence ends (Maitland 2011). Biodiversity benefits within fenced peninsulas have been reported to some extent, for instance, removal of invasive mammalian predators from Hawaii’s Ka’ena Point Natural Area Reserve has increased abundance and reproduction of nesting wedge‐tailed Shearwaters ( Puffinus pacificus ; VanderWerf et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This includes peninsula‐fenced ecosanctuaries: pest‐exclusion fencing at the peninsula neck aims to maintain low or close‐to‐zero pest abundance, despite potential reinvasion around the coastal fence ends (Maitland 2011). Biodiversity benefits within fenced peninsulas have been reported to some extent, for instance, removal of invasive mammalian predators from Hawaii’s Ka’ena Point Natural Area Reserve has increased abundance and reproduction of nesting wedge‐tailed Shearwaters ( Puffinus pacificus ; VanderWerf et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, none of the seabird colonies were established by translocation and only one, that of Monteiro's storm-petrel Hydrobates monteiro on Praia, witnessed a conservation intervention, namely provision of extra nest-boxes, that might have influenced population change after invasive eradication. With one exception, the growth of the wedgetailed shearwater Puffinus pacificus colony at Kaena Point, Oahu, Hawaii (VanderWerf et al, 2014), the data come from relatively small islands (<300 km 2 ), and not 'inland islands' protected by predator-proof fences.…”
Section: Data Collationmentioning
confidence: 99%
“…In fact, the dramatic increase in some shearwaters' breeding population immediately following rat eradication (Bourgeois et al 2013;Marie et al 2014;VanderWerf et al 2014) suggested that procellariid seabirds may select their breeding sites according to direct cues. However, we hypothesized that this selection could also be at least partially driven by olfaction (avoidance of burrows 'smelling' of rats), with a predation risk assessment based upon predator chemical cues.…”
Section: Discussionmentioning
confidence: 98%